Doxorubicin bound to a HPMA copolymer carrier through hydrazone bond is effective also in a cancer cell line with a limited content of lysosomes - Ríhová, B; Etrych, T; Pechar, M; Jelínková, M; Stastný, M; Hovorka, O; Kovár, M; Ulbrich, K (Journal of controlled release, 2001)
We have synthesized conjugates containing doxorubicin (DOX) bound to oligopeptide side chains (GlyGly or GlyPheLeuGly) of a water-soluble copolymer carrier based on poly[N-(2-hydroxypropyl)methacrylamide] (PHPMA) either through proteolytically (PK1 conjugates) [Synthetic polymeric drugs. U.S. Patent 5,037,883 (1991)] or hydrolytically cleavable bond (HC conjugates). Pharmacological efficacy of PK1 and HC conjugates was compared in vitro on murine: T-cell lymphoma EL4, B-cell leukemia BCL1, B-cell lymphoma 38C13, leukemia P388 and Con A-stimulated A/Ph splenocytes and on human: primary (SW480) and metastatic (SW620) colorectal cancer cell lines parent and transfected with Thy 1.2 gene [2] and on erythromyeloid leukemia cell line K 562. Inhibition of proliferation determined by 3[H]-thymidine incorporation revealed that the cytostatic effect of HC conjugates is up to two orders of magnitude higher compared to PK1 conjugates. In some cancer cell lines (SW 620/T, SW 480) the pharmacological activity of HC conjugates is in vitro comparable with the activity of the free drug. Unlike PK1 conjugates, HC conjugates with a lysosomally degradable spacer (GlyPheLeuGly) are less effective compared to HC conjugates containing lysosomally non-degradable spacer (GlyGly). Moreover, HC conjugates exert pronounced anti-proliferative activity also in erythroblastoid leukemia cell line K 562 with a limited content of lysosomes.
Keywords: methakryláty; Lysosomes; Tumor Cells, Cultured; Oligopeptides; Drug Carriers; molekulová hmotnost; doxorubicin; hydrazony; Doxorubicin; Molecular Weight; zvířata; myši; oligopeptidy; Mice; nádorové buňky kultivované; Polymethacrylic Acids; Hydrazones; Spleen; Neoplasms; nosiče léků; nádory; lyzozomy; Animals; kyseliny polymethakrylové; Methacrylates; Antibiotics, Antineoplastic; slezina; protinádorová antibiotika